Gifted children and their peers perceived parental attitudes, psychosocial problems and quality of life - Yildiz, Sümeyye; Altay, Naime (Publishing Office of the University of Rzeszow, 2024)
Introduction and aim. Gifted children are defined as extraordinary children due to their high level of intelligence and specific skills. This study aimed to examine gifted children and their peers perceived parental attitudes, quality of life (QoL), and psychosocial problems. Material and methods. The study sample consisted of two groups: (1) gifted children (study group) and their parents and (2) peers (control group) and their parents. Data were collected using a descriptive characteristics form, the parental attitude scale (PAS), the pictorial pediatric symptom checklist (PPSC) and the pediatric quality of life inventory (PedsQL). Results. Both groups were similar in terms of age, gender and grade level. It was mostly the mothers who completed the data collection forms. The study and control groups had a mean PAS score of 94.18±0.738 and 99.31±0.798, respectively and a mean PPSC score of 16.11±0.475 and 16.76±0.480, respectively. The study and control groups had a mean QLS score of 83.19±0.70 and 80.28±0.83, respectively. There was a weak positive correlation between the PAS and PPSC scores (r=0.92; p<0.166). Conclusion. It is recommended that parental attitudes and their effects on children’s psychosocial status and QoL be monitored and that parents be supported. Parental attitudes and a child’s psychosocial and behavioral problems and QoL levels should be assessed to by health professionals be able to improve the well-being of both children and their parents.
The study was approved by the Ethics Committee of the university (77082166-302.08.01).
Keywords: gifted children; parental attitudes; pediatric nursing; psychosocial problems and quality of life